2014
DOI: 10.1080/13504509.2014.946543
|View full text |Cite
|
Sign up to set email alerts
|

Forest dependence and income inequality in rural Ethiopia: evidence from Chilimo-Gaji community forest users

Abstract: The aim of the study was to examine the determinants of forest dependence and the role of community forest on income inequality in rural Ethiopia. Regression results, using Heckman's two-stage estimation method, suggest that the probability of households' participation in low-return forest activities is determined by farm size, number of male members in the household and distance from the forest plot to the household's homestead. Further, the likelihood of households' participation in high-return forest activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…Rural households in the developing world derive significant part of their livelihoods from forest resources (Adhikari et al 2004;Adhikari 2005;Sunderlin et al 2005;Mamo et al 2007;Babulo et al 2008Babulo et al , 2009Appiah et al 2009;Gobeze et al 2009;Gatiso and Wossen 2014;Wunder et al 2014;Dash et al 2016).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rural households in the developing world derive significant part of their livelihoods from forest resources (Adhikari et al 2004;Adhikari 2005;Sunderlin et al 2005;Mamo et al 2007;Babulo et al 2008Babulo et al , 2009Appiah et al 2009;Gobeze et al 2009;Gatiso and Wossen 2014;Wunder et al 2014;Dash et al 2016).…”
Section: Introductionmentioning
confidence: 99%
“…1 It is also well documented that the rural poor obtain major part of their household income from natural resources than their better-off counterparts (Narain et al 2008;Gatiso and Wossen 2014). Moreover, studies show that the major part of the forest income comes from natural forests .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In their study carried out in 24 developing countries, Angelsen et al (2014) found that environmental incomes account for 28% of the total household income. Moreover, the importance of environmental and non-environmental incomes on reducing poverty and income inequality have been investigated in many developing countries, including South Africa (Thondhlana and Muchapondwa 2014b), Ethiopia (Gatiso and Wossen 2015), Cambodia (Nguyen et al 2015), Zimbabwe (Cavendish 2000), and Nicaragua (Ravnborg 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The results of the case studies have varied because of the diversity of social, economic, ecological, and political contexts. Nevertheless, environmental incomes have been shown to contribute to poverty alleviation and to reducing income inequality (Gatiso and Wossen, 2015;Thondhlana and Muchapondwa, 2014a). Environmental income is also expected to be a safety net against poverty (Shackleton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%